Effect of pH and temperature in production of mycotoxins and antibiotics by phytopathogenic moulds for Persian lime (Citrus latifolia T.) in a complex lime pericarp-base medium - Contreras, Teresa Sandoval-; López, Angélica Villarruel-; Beltrán, Arturo Pedro Sierra-; Vitela, Refugio Torres-; Ascencio, Felipe (Emirates Journal of Food and Agriculture, 2017)
Post-harvest decay of citrus fruits is caused by moulds capable of producing mycotoxins with great impact on health. The objective of this study was to determine the effect of pH and temperature in synthesis of mycotoxins and antibiotics in Persian lime pathogenic and mycotoxigenic moulds, and to investigate the diffusion of mycotoxins inside the citrus fruit. As a result, several mycotoxins were identified, such as aflatoxins and fumonisins. In most of the analysed moulds, synthesis of the secondary metabolites was observed on acidic pH at 20 °C; some antibiotics were found as well. Diffusion of A. niger mycotoxins and antibiotics was observed in the interior of the lime fruit, achieving highest concentration in the septa. Knowing the behaviour of these moulds is useful for evaluation of health risk due to mycotoxins and control of pathogenic and mycotoxigenic post-harvest moulds.